PENGABDIAN KEPADA MASYARAKAT PADA SISWA SMA NEGERI 2 KAUR DALAM EDUKASI KELAS INSPIRASI KIAT SUKSES BEASISWA DAN STUDI KE LUAR NEGERI - Arono Arono; Nadrah Nadrah; Ade Sisca Villia; Syahriman Syahriman; Furqan Al Qowi; Asyraf Ramadhab Al Qowi (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Various factors influence students in further study abroad with scholarships, including motivation, social, cultural, educational, economic, and efforts that have been or can be made. This community service is carried out with the aim of describing and expressing the various motivations, factors and efforts that have been and will be made in preparing to study abroad on a scholarship. The service method is carried out using a qualitative descriptive approach using the APTE model (situation analysis, training, action and evaluation). The service carried out with inspirational class education on tips for success in overseas scholarships has high motivation to continue studying abroad due to need, sufficient supporting factors such as family, society and the economy, and the efforts made are still low in searching for information, preparing documents, and following the requirements so that adequate intensity of guidance and training is still needed from families, teachers and the school. The implementation of inspiration class education runs well and smoothly using the APTE model. The evaluation referred to in this training consists of initial evaluation, implementation evaluation (process), and final evaluation in the form of training participant responses with good results.